Career development and learning pathways of Paralympic coaches with a disability - Douglas, S.; Falcão, W. R.; Bloom, G. A. (Adapted Physical Activity Quarterly, 2023)
The purpose of this study was to gain an understanding of the career development and learning pathways of Paralympic head coaches who previously competed as Paralympic athletes. Each coach participated in a semistructured interview. A thematic analysis of the data revealed three higher order themes, which were called becoming a coach, learning to coach, and lifelong learning and teaching. Across these themes, participants discussed interactions with other coaches and athletes with a disability, learning from mentors and coaching clinics, as well as limited formal educational opportunities they experienced transitioning from athlete to head coach. The findings revealed that they acquired most of their knowledge from a combination of knowledge gained as athletes and informal sources, including trial and error. They also stressed the need for enhanced recruiting of parasport coaches and parasport coach education opportunities that would enhance programs for athletes with physical disabilities, from grassroots to Paralympic levels.